Developing the Key Attributes for Product Matching Based on the Item’s Image Tag Comparison - Cherednichenko, Olga; Yanholenko, Olha; Kanishcheva, Olga (My University, 2020)
With the constant growth of the number of products on e-marketplaces, buyers feel hard to find and choose items that would satisfy all their needs and expectations. Search and filtering algorithms of recommender systems, although are striving to help users, still fail quite often due to incomplete and inaccurate description of items. The given work suggests to combine analysis of both item description and item image in order to construct groups of similar items. Since a person can define whether two items are similar or not looking at two images and a brief description, it is suggested to form a set of similar items based on users’ judgments and then to extract the core of keywords for the specific type of products. Further, it is proposed to use the given core to evaluate the similarity of any new item added to the definite group. The case study deals with the building of the core of keywords for sneakers. The developed key attributes allow matching the items with a high precision, thus, proving the effectiveness of the method of the core construction.
Keywords: e-commerce; item's Images; similarity items; image similarity; images matching; tag similarity; key attributes